2016
DOI: 10.1371/journal.pone.0164070
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Reference Genes for Quantitative Real Time PCR Assays in Aortic Tissue of Syrian Hamsters with Bicuspid Aortic Valve

Abstract: Bicuspid aortic valve (BAV) is the most frequent congenital cardiac malformation in humans, and appears frequently associated with dilatation of the ascending aorta. This association is likely the result of a common aetiology. Currently, a Syrian hamster strain with a relatively high (∼40%) incidence of BAV constitutes the only spontaneous animal model of BAV disease. The characterization of molecular alterations in the aorta of hamsters with BAV may serve to identify pathophysiological mechanisms and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Hence, the identification of suitable RGs is an essential step in qPCR analysis, since the selection of unstable genes for normalization could result in misleading conclusions. The number of publications reporting the validation of RGs for normalization of RT-qPCR studies has increased in different scientific research disciplines including: microbiology 25 27 , cancer 28 – 30 , plant sciences 31 33 , neurosciences 34 , and also cardiovascular research 35 , 36 . In endocrine research certain studies pertaining to obesity and diabetes have characterized most stable RGs for qPCR normalization purposes 37 39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the identification of suitable RGs is an essential step in qPCR analysis, since the selection of unstable genes for normalization could result in misleading conclusions. The number of publications reporting the validation of RGs for normalization of RT-qPCR studies has increased in different scientific research disciplines including: microbiology 25 27 , cancer 28 – 30 , plant sciences 31 33 , neurosciences 34 , and also cardiovascular research 35 , 36 . In endocrine research certain studies pertaining to obesity and diabetes have characterized most stable RGs for qPCR normalization purposes 37 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The four algorithms considered as gold standard for determination of the stability of gene expression are Genorm, NormFinder, BestKeeper and ΔCt 36 . GeNorm calculates gene stability based on the arithmetic means of all pair-wise comparisons, but does not correct co-regulated genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When additional data from the other program were incorporated through RefFinder, this shifted to Actb, Hprt1, RpI13a and Tubb in the lung, liver, spleen and pancreas respectively. A previous study using only GeNorm identified Cdkn1and G3pdh as the most appropriate housekeeping genes in aortic tissue of Syrian hamsters (Rueda-Martinez et al 2016). Given the differences we found between GeNorm and RefFinder, it may be appropriate to reevaluate these findings with additional methods.…”
Section: Appropriateness Of Housekeeping Genesmentioning
confidence: 80%
“…According to previous studies in rodents, nine candidate reference genes were selected [ 16 , 17 , 18 , 19 ]. Gapdh and β-actin are classic reference genes in various species, and Hprt1 , Rpl13a , Tbp , Sdha , Hmbs , PPIA , and B2M are high-frequency reference genes in rodents.…”
Section: Methodsmentioning
confidence: 99%